Histological analysis of motoneuron survival and microglia inhibition after nerve root avulsion treated with nerve graft implantation and minocycline: an experimental study - Faizul H. Ghazali,; Wutian, Wu; Jafri M. Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Motor vehicle accidents are the most common cause of injuries involving avulsion of the brachial plexus in humans, resulting in debilitating motor dysfunction. Lack of an established animal model to test drug treatments hinders the introduction of new pharmacological agents. Avulsion injury of cervical ventral roots can be replicated in rats, resulting in a progressive loss of the motoneurons and increase in neurotoxic expression of microglia. This is a report on the effect of prompt nerve implantation and minocycline treatment on the suppression of microglia activation and survival of motoneurons. 20 adult female Sprague-Dawley rats were used for this study, which was approved by the Animal Ethical Committee, USM (approval number /2011/(73)(346)). The animals underwent surgical avulsion of the C6 nerve root, followed by reimplantation with peripheral nerve graft and treatment with intraperitoneal minocycline. At 6 weeks postoperatively, immunohistochemistry using primary antibody Iba1 (microglia) and nicotinamide adenine dinucleotide phosphate diaphorase (NADPh) with neutral-red staining (motoneuron) under flourescence microscopy was performed at the C6 spinal cord segment and then quantified. This study showed signifi cant reduction of microglia expression in the study group; mean ranks of control and study group were 15.2 and 11.6, respectively; U=9.5, Z=3.02, p<0.05. However, this did not translate into a signifi cant increase of motoneuron survival in the combined group; the mean ranks of control and study group were 40.6 and 41.6, respectively; U=44.5, Z=-.0378, p>0.05. This may be due to the effect of the surgery; the surgery has the potential to cause additional trauma to the cord parenchyma, leading to further motoneuron loss and an increase in scarring around the avulsed region, thus impeding regeneration of the motoneuron.